“Life of St. Sava” by Theodosius of Chilandar as a historical source on Strez, the ruler of Prosek - Wolski, Jan (Balcanica Posnaniensia. Acta et studia, 2012)
The late XII and the early XIII c. were a period of important political changes on the Balkan Peninsula. Strez (1207-1214) was one of the local rulers which emerged in the mountain regions of the central Balkans in that time. We know the outline of his life from the sources such as: “Life of St. Symeon” by Stefan the First-Crowned, “Life of St. Sava” by Domentijan, “Life of St. Sava” by Theodosius of Chilandar and the letter of the Latin Emperor Henry from the January of 1212 or 1213. The paper presented here is divided into two parts. In the first part the Author presents the sources mentioned above and discusses major problems concerning their interpretation: the chronology of Strez’s life, territorial extent of his state, relations with the neighbor countries and circumstances surrounding his death. The second part comprises translation of the excerpt about Strez from the “Life of St. Sava” by Theodosius of Chilandar.